Comparison of hemocoagulase atrox versus tranexamic acid used in primary total knee arthroplasty: A randomized controlled trial. Issue 188 (April 2020) - Qin, Ji-zheng; Wang, Shao-jie; Zheng, Xin-peng; Zhao, Hong-hai; Lin, Yuan; Shi, Lei; Xia, Chun
Abstract: Background: Total knee arthroplasty (TKA) has been considered as an effective choice for end-stage osteoarthritis or rheumatic arthritis. Tranexamic acid (TXA) has been widely used to prevent excessive blood loss perioperatively. Similarly, hemocoagulase atrox can significantly diminish blood loss and transfusion requirements in surgeries, however, it was rarely used in TKA. The purpose of this study is to identify whether hemocoagulase atrox is equal to TXA in reducing blood loss and transfusion rates following TKA, and compare clinical outcomes and complications between the two groups. Methods: 74 patients were randomized to receive TXA (1.5 g intra-articular combined with 1.5 g intravenous), or hemocoagulase atrox (1 U intra-articular combined with 1 U intravenous). The primary outcome was total blood loss. The secondary outcomes included reduction of hemoglobin concentration, clinical outcomes, blood coagulation values, thromboembolic complications, and transfusion rates. Results: The mean total blood loss was 431.7 mL in the TXA group compared with 644.6 mL in the hemocoagulase atrox group, with statistical significance ( P  < 0.05). There were significant differences in reduction of hemoglobin level ( P  < 0.05). The rate of deep vein thrombosis (DVT) in patients given TXA was higher than those given hemocoagulase atrox, however, there were no significant differences. No transfusions were required in either group, and no significant differences were found in the length of hospital stay and clinical outcomes. Conclusions: Although the blood loss was significantly greater in the hemocoagulase atrox group, no transfusions were required and no significant differences were observed for any other outcomes measured. Meanwhile, the rate of DVT in the hemocoagulase atrox group tends to be lower than those in TXA group. We concluded that hemocoagulase atrox was not superior to TXA in reducing perioperative blood loss. Further studies are warranted to evaluate if hemocoagulase atrox use could improve perioperative blood loss in patients with high thrombotic risk undergoing TKA. Highlights: Hemocoagulase atrox shows clinical outcomes similar to tranexamic acid. Hemocoagulase atrox does not increase the rate of deep vein thrombosis. Hemocoagulase atrox can reduce blood loss in total knee arthroplasty.